A Hitherto Undescribed Congenital Haemorrhagic Diathesis Probably Due to Fibrin Stabilizing Factor Deficiency - Duckert, F; Jung, E; Shmerling, D. H (Thrombosis and Haemostasis, 1961)
A new congenital haemorrhagic diathesis is described. It is characterized by the poor and slaw wound healing, profuse and long bleeding and by probable absence of spontaneous and joint bleeding. It is due to the deficiency of a factor which makes the fibrin clots insoluble in urea. This factor is probably the fibrin stabilizing factor of Laki and Lorand, although no proof of their identity can yet be given. The deficiency appears in both sexes and is probably an autosomal recessive disease.